اثر استراتيجية المهام الجزئية (جيكسو) في تنمية مهارات الاطباق الزخرفية لدى طلبة قسم التربية الفنية (Journal of the College of Basic Education, 2024)
Through the field experience of the researcher for being a professor of Arabic calligraphy and Islamic decoration, he found there is a deficiency in learning the skills of decorative dishes, resulting in a weakness in the level of skill performance of students of the second stage of the morning study in the skills of star dishes, especially since decorative dishes are a mathematical system based on geometric shapes, so the researcher believes that the strategy of partial tasks increases the effectiveness of students in the implementation of classroom activities in learning the skills of star dishes. Research Objective: The current research aims at the following: What is the impact of the partial tasks strategy (JEXO) on the development of decorative dishes skills among students of the Department of Art Education. Research hypotheses: There is no statistically significant difference at the level of significance (5%) between the average scores of the experimental group that were studied according to the strategy of fragmentary tasks and the average scores of the control group that were studied according to the usual method in the post-test. There is no statistically significant difference at the level of significance (5%) between the average scores of males in the experimental group that were studied according to the strategy of fragmented tasks and the average score of females in the experimenta group .